SPECIALITIES FEATURES OF THE KIEV SPELESTO-RECREATIONAL OBJECTS RESERVATION - КОЦЮБА, А. І. (Man and Environment. Issues of Neoecology, 1970)
Distinguishes types of man-made underground cavities that can be used for recreation and tourism. The analysis of existing sacred, transport, engineering and separate military wing formations that are typical for this area. Their methodological research within the capital. Shown the basic concept of "spelestorekreaty" and listed to the characteristics of the activity based on territorial characteristics. Determined general spelesto and recreational facilities that are currently used in the recreation and tourism in Kyiv. Shown features of protection and rational use spelesto-recreation formations in the area of Kyiv. Great attention is paid to museumification of some underground man-made structures that can later be used for visiting local residents and guests of the city.